Contestations Over Classifications: Latinos, the Census and Race in the United States - Clara E. Rodríguez (Journal de la Société des Américanistes)
Contestations over classifications: Latinos, the census and race in the United States. The divergence between popular and state classifications of peoples has become increasingly important with the growing migration of peoples around the world. This paper examines this issue by focusing on one group (Latinos in the US) at one historical juncture (the late 20th-early 21st centuries). After examining the evolution of US census « race » categories in the context of shifting political, economic, and scientific trends, it reviews Hispanic/Latinos’ responses to questions of « race » on the US census and the theories that have surfaced to explain why so many Latinos choose the « Some Other Race » category on the census. It also chronicles the US government’s efforts to discourage such responses and force Latinos into more traditional US race categories. The global uniqueness of the US’s « race » concept is also underscored.